The Impact of Total Quality Management Implementation on Student Achievement at SMP Education 21 Kulim Pekanbaru - Dyana Maftuhatu Rosyidah; Jabar, Cepi Safruddin Abd.; Fitria, Roudhotul; Yolviansyah, Fauziah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to identify methods and procedures for implementing Total Quality Management (TQM) in schools and analyze the results related to student achievement. The research employs a qualitative method with data collection techniques including interviews, observations, and documentation, and ensures data validity through technique and source triangulation. Data analysis is conducted using interactive analysis, which includes data collection, data display, data reduction, and conclusion drawing. The results indicate that TQM implementation at the school has successfully improved student achievement through effective teaching methods, active student participation, and good collaboration among teachers, students, and parents. The application of TQM can be an effective approach to enhancing the quality of education in schools